Are theory of mind and bullying separately associated with later academic performance among preadolescents?. (27th December 2018) - Clemmensen, Lars; Jepsen, Jens Richardt Møllegaard; van Os, Jim; Blijd‐Hoogewys, Els M. A.; Rimvall, Martin K.; Olsen, Else Marie; Rask, Charlotte U.; Bartels‐Velthuis, Agna A.; Skovgaard, Anne Mette; Jeppesen, Pia
Abstract : Background: Bullying and poor theory of mind (ToM) are both considered to negatively impact academic performance. However, it is unclear if they have separate effects. Aim: The aim of the current study was to examine the potentially separate associations of bullying and ToM with academic performance. Sample: A general population sample of 1, 170 children aged 11–12 years. Methods: Information on bullying, type of involvement (none, victim (only), bully (only), victim–bully (both)), ToM, and estimated intelligence was obtained at face‐to‐face assessments. Information on academic performance was obtained from Danish school registers. Results: ToM was positively associated with academic performance, and involvement in bullying was negatively associated with academic performance. Academic performance differed between types of involvement in bullying. Pairwise post hoc analyses showed that in the full sample, the only significant difference was between those not involved and those involved as victim (only). This was also the case for girls. Adjusting for potential shared variance with gender, estimated intelligence and ToM being victim (only) and victim–bully (both) were negatively associated with academic performance compared to no involvement. Thus, being a victim (or victim–bully) contributes negatively to academic performance beyond the effects of ToM and intelligence, and regardless of gender. Similarly, ToM remained positively associated with academic performance after adjusting for shared variance. Conclusion: ToM and involvement in bullying were both separately associated with later academic performance. These results remained even after adjusting for shared variance, and for shared variance with gender and estimated IQ.